The capacity and efficacy of security agencies in combating terrorism in the democratic South Africa - Ndou, Oliver (Centre for Law and Society, 2026)
Terrorism is a complex phenomenon that requires a complex response that involves state capacity and partnership between countries. It poses a threat to global stability because it undermines democratic architecture. Worldwide, terrorism has inflicted significant loss of life, destabilised governments, and created humanitarian crises. In Africa, it presents another dilemma. Countries around the Horn of Africa, such as Somalia, in West Africa, and the Sahel states such as Mali are bedeviled by the existence of groups such as Al-Shabaab, ISIS, and Boko Haram. South Africa is also facing terrorism challenges. It has been used as a helipad for terrorism financing and a transit point because of its complex financial institutions and its perceived incapacity to deal with this phenomenon. The aim and objectives of this research were to determine the capacity and efficacy of security agencies in combating terrorism in democratic South Africa. The research further analysed the manifestation of domestic and international terrorism as perceived in South Africa. Furthermore, a comparative overview of counter-terrorism measures from developed and developing countries was evaluated as a flagship for the South African context. Qualitative research was used in the collection of data. The population was derived from a sample of terrorism and security experts who know the subject matter. Various research tools were developed for collecting data, and these included interviews, questionnaires, recording devices, and document analysis. An interactive qualitative analysis of data was used. The research confirmed that the security agencies are not well-capacitated to combat terrorism in South Africa. However, the research recommended that an integrated, holistic approach is necessary to combat terrorism through collaboration among the various departments of the security agencies.